The Influence of Profitability and Funding Policy on Dividend Policy and Its Impact on Profit Growth - Budi Prijanto; Agustin Rusiana Sari; Fera Riske Anggita; Irwan Moridu; Suseno Suseno (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to examine the effect of profitability and funding policies on dividend policy and their impact on profit growth (study of food and beverage companies listed on the IDX). The population in this study are food and beverage companies listed on the IDX as many as 30 issuers. The sample obtained using purposive sampling with predetermined criteria so that 10 companies can be collected with a total of 50 financial statements. The type of data is secondary data sourced from financial reports and annual reports. The data analysis method used in this study is the classical assumption test, the coefficient of determination test (R2), multiple linear regression tests, and hypothesis testing using multiple linear analysis. The results of the study show that profitability has a significant effect on dividend policy, while funding policy has no significant effect on dividend policy. Significant profit growth mediates the effect of profitability on dividend policy, while not significantly mediates the effect of funding policy on dividend policy.